2003
DOI: 10.1038/sj.bjp.0705087
|View full text |Cite
|
Sign up to set email alerts
|

The ACh‐induced contraction in rat aortas is mediated by the Cys Lt1 receptor via intracellular calcium mobilization in smooth muscle cells

Abstract: 1 Our previously published data indicate that an endogenously produced 5-lipoxygenase metabolite can strongly contract isolated endothelium-preserved rat aortic strips when cyclo-oxygenase isoenzymes are inhibited. Therefore, we decided to investigate if cysteinyl-containing leukotrienes (Cys Lts) are involved in this endothelium-dependent contraction. 2 The isometric contraction of endothelium-preserved rat aortic strips was recorded in preparations preincubated with 5 mM indomethacin and precontracted with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
7
19
1
Order By: Relevance
“…In all experiments, only cells at P2 of culture were used. Detailed procedures used for rASCs, rat coronary endothelial cells (Failli et al, 2000) and rat aortic smooth muscle cells (Mazzetti et al, 2003) were described in the Supplementary material.…”
Section: Cell Preparation and Characterizationmentioning
confidence: 99%
“…In all experiments, only cells at P2 of culture were used. Detailed procedures used for rASCs, rat coronary endothelial cells (Failli et al, 2000) and rat aortic smooth muscle cells (Mazzetti et al, 2003) were described in the Supplementary material.…”
Section: Cell Preparation and Characterizationmentioning
confidence: 99%
“…The leukotriene synthesis inhibitor and cysLT antagonist attenuate ACh-induced contraction in rabbit coronary artery [18]. More recently, Mazzeti and colleagues [19] reported that, in the presence of indomethacin, cysLT receptor antagonists blocked the endothelium-dependent contraction to ACh in aorta from normotensive rats.…”
Section: Introductionmentioning
confidence: 98%
“…After 60 min of stabilization, the absence of endothelium was tested as previously reported [18], and cumulative concentration-response curves of AT-II or ET-1 were performed in different aortic preparations. Then, strips were extensively washed, re-stabilized and precontracted using the maximal contracting dose of AT-II or ET-1 (100 % of contractile response).…”
Section: Synthesis Of Corm-3 and Other Chemicalsmentioning
confidence: 99%